Adjustment of Foreign Emission Impacts on Provincial PM2.5 Concentrations in South Korea based on Upwind Observations and Estimation of Domestic Emission Uncertainty 풍상 관측 기반 2019년 국내 시도별 PM2.5 국외 배출 영향 보정 및 국내 배출량의 불확도 추정 - Bae, Minah; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2022)
In this study, we estimated the foreign emission impact on PM2.5 concentration in South Korea using Weather Research and Forecasting (WRF)-Community Multiscale Air Quality (CMAQ) modeling with a set of bottom-up emissions inventories over Northeast Asia during 2019. PM2.5 foreign impact based on the emissions inventory was estimated to 12.7 μg/m3 for the study period. However, when compared to the PM2.5 observations in China, simulated PM2.5 concentration for the period was overestimated by about 10 μg/m33 (24%) during 2019. When adjusted with ratios of monthly mean observed to simulated concentrations over the upwind region, the period mean foreign impact was lowered by 2.6 μg/m33. The relative foreign impacts in South Korea before and after the adjustment was 54% and 43%, respectively. On the other hand, the bias between observed and simulated PM2.5 concentrations in South Korea has increased from 0.1 μg/m33 before foreign contribution adjustment to -2.5 μg/m33 after the adjustment. This indicates that additional domestic emissions are necessary to explain the lack of PM2.5 self-contribution (2.5 μg/m33). After the adjustment, the biases between the observations and simulated concentrations for seventeen provinces ranged from -10.5 to 24.5 μg/m33. This result represents that accuracy of provincial level emissions should be guaranteed when future direction on the sub-regional air quality managements in South Korea to lower the ambient concentration of the secondary air pollutant is considered. Overall, this study exhibits that uncertainties in foreign contributions need to be better understood prior to estimation of uncertainties embedded in domestic emissions in South Korea to weigh the importance of PM2.5 transboundary impact.
Keywords: Adjustment; Capss; Emission uncertainty; Foreign emission impacts; Pm2.5